Fruiting Body | SMFA Senior Thesis May 2018. - Coppola, Renee. (Tufts Archival Research Center, 2018)
An animation embedded in a soft fabric sculpture that also provides seating.; Keywords: Fruit/agriculture, sexuality, female reproductive system, digital matrix conspiracy theory.